Peningkatan Hasil Belajar Siswa Pada Materi IPA Tentang Alat Pencernaan Manusia Melalui Media Puzzle - Ernawati Ernawati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
In the learning process can not be separated from the ability of teachers in using creative and innovative learning media in order to provide stimulus to students to be more active in following the learning process. Monotonous teaching and learning process can have an impact on students who do not have learning motivation and impact on low student learning outcomes. This research aims to find out the improvement of students' learning outcomes on IPA material about human digestive devices through the medium of puzzles. Based on observations in the process of learning IPA material human digestive equipment, one of the obstacles is the lack of understanding of students about digestive device material. This study uses the medium of puzzle of human digestive devices. This research is expected to be useful for the improvement and improvement of the implementation of IPA learning. Based on the results of observations and discussions obtained that: through the use of puzzle media can improve the results of learning IPA about the human digestive devices.